Clement of Alexandria's Stromata in the Early 16th Century. - Galán Vioque, Guillermo (Mnemosyne, 2023)
This article examines the citations from Clement of Alexandria's Stromata prior to the editio princeps by Piero Vettori (1550) and provides new data on the relationship between that edition and the manuscripts that have preserved this work for future generations.